LIVING SUNNAH IN LOCAL CONTEXT: The Practice of Two Calls (Azan) for Fajr Prayer at al-Furqan Mosque, Banjarmasin (RIWAYAH, 2025)
The practice of delivering the dawn call to prayer (azān Subuh) twice at the Al-Furqan Mosque in Bumi Mas Raya, Banjarmasin, represents a form of living sunnah—the contextualized enactment of the Prophet Muhammad’s traditions within a specific local setting. This study aims to examine the implementation of this practice, explore community perceptions, and identify the educational values embedded within it. Employing a qualitative descriptive approach, data were collected through in-depth interviews with mosque administrators, staff, and congregants, as well as through direct observation and document analysis, including official azan schedules. The findings reveal that the first azān functions as a preparatory reminder for the dawn prayer, while the second marks its actual commencement. The community largely supports this practice, although most are unfamiliar with its basis in hadith literature. Beyond its ritual function, the practice holds significant educational value, fostering spiritual discipline and promoting ethical, social, cultural, psychological, physical, and familial development. This study contributes to the discourse on living sunnah by highlighting how prophetic traditions continue to be interpreted and embodied within contemporary Muslim communities, reflecting dynamic interactions between textual heritage and local religious life. [Praktik pelafalan azan Subuh sebanyak dua kali di Masjid Al-Furqan, Bumi Mas Raya, Banjarmasin, merupakan bentuk living sunnah—yakni penerapan tradisi Nabi Muhammad yang dikontekstualisasikan sesuai dengan realitas lokal. Penelitian ini bertujuan untuk mengkaji pelaksanaan praktik tersebut, memahami persepsi masyarakat, serta mengidentifikasi nilai-nilai edukatif yang terkandung di dalamnya. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam dengan pengurus masjid, petugas, dan jamaah sekitar, serta melalui observasi langsung dan analisis dokumen, termasuk jadwal azan resmi. Temuan menunjukkan bahwa azan pertama berfungsi sebagai pengingat untuk mempersiapkan diri dalam beribadah, sedangkan azan kedua menandai masuknya waktu salat Subuh. Masyarakat secara umum menerima praktik ini dengan baik, meskipun sebagian besar tidak mengetahui dasar rujukan hadisnya. Lebih dari sekadar fungsi ritual, praktik ini memiliki nilai edukatif yang signifikan, mendorong kedisiplinan spiritual serta menguatkan aspek etika, sosial, budaya, psikologis, fisik, dan keluarga. Studi ini memberikan kontribusi terhadap wacana living sunnah dengan menunjukkan bagaimana tradisi kenabian terus diinterpretasikan dan dihidupkan dalam kehidupan masyarakat Muslim kontemporer, mencerminkan interaksi dinamis antara warisan tekstual dan praktik religius lokal.]